Nordic Mining School (NMS) for advanced extractive technology and natural resources managment : a joint Luleå University of Technology and Oulu University initiative - Weihed, Pär; Gehör, Seppo; Nordlund, Erling; Pålsson, Bertil; Vikstedt, Helen; Ylineimi, Leen; Öhlander, Björn (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2009)
Godkänd; 2009; 20091218 (andbra)